The Antioxidant Properties and Chemical Composition of Stachys inflata Benth Leaves Grown Wild in Lorestan Province - Hassan Ahmadvand; Sima Farajollahi *; Hamze Amiri; Ali Amiri (Lorestan University of Medical Sciences, 2017)
Background and Aim: In recent years there has been an increasing interest in herbal medicines and natural antioxidant products to be used as medicines and food additives. The present research identified the various antioxidative activities of ethanol and methanol extracts, and chemical composition of Stachys inflate Benth leaves essential oil. Materials and Methods: This experimental study was carried out in 2015 in Lorestan University of Medical Sciences. Ethanol and methanol extracts of Stachys inflata Benth leaves were primarily prepared. The total antioxidant capacity of samples was assessed by phosphomolybdate method. Total phenol content and total flavonoid content were determined by Folin-Ciocalteu and Zhishen methods. The components of Stachys inflate Benth leaves essential oil were analyzed with gas chromatography/mass spectrometry (GC/MS). Results: It was demonstrated that the total antioxidant capacity of ethanol and methanol extracts of Stachys inflata Benth leaves were 4.30±0.17; 3.63±0.23 mg of ascorbic acid equivalents /g of extract. Moreover, the total phenol content ethanol and methanol extracts of Stachys inflata Benth leaves were 830.334±26.41; 384.29±13.37mg of gallic acid equivalents /g of extract, and flavonoid content ethanol and methanol extracts of Stachys inflata Benth leaves were 17.09±0.154; 31.18±1.03 mg of quercetin equivalents /g of extract. GC/MS data and retention indices of Stachys inflate Benth leaves essential oil samples were used to identify 54 constituents. These compounds make up a total of 48.87 percent essential oil. Phenol, 2-methyl-5(1-methyleth; Phenol, 5-methyl-2-(1methyleyth; 2-pentadecanone and hexadecanoic acid are the major compounds of Stachys inflate Benth leaves essential oil. This study indicated that Stachys inflate Benth leaves essential oil has remarkable antioxidant properties. Furthermore,  Stachys inflate Benth leaves essential oil was identified as an easily accessible source of natural antioxidants such as Phenol,2-methyl-5(1-methyleth; Phenol,5-methyl-2-(1methyleyth; 2-pentadecanone,6,10,14-trimet; Veridi florol; 2-cycohexen-1-on,2-methyl-5- and 1H-cycloprop[e]azulen-7-ol,dec. It may also be suitable to be used in food and pharmaceutical applications. Conclusion: This study demonstrated that Stachys inflata Benth leaves are easily accessible sources of natural antioxidants. Therefore, they may be suitable to be used in food and pharmaceutical applications.